Evaluasi Penggunaan Pupuk Hayati pada Pertumbuhan Tanaman Alpukat (Persea americana Mill.) di Kebun Superavo, Subang: Evaluation of the Use of Biofertilizer on the Growth of Avocado Plants (Persea americana Mill.) at Superavo Orchard, Subang - Fahrizal Hazra; Dwi Andreas Santosa (Jurnal Ilmu Tanah dan Lingkungan, 2022)
Increasing the amount of avocado production is influenced by the effectiveness of fertilization. Fertilization is the most important thing in agriculture to improve plant nutrition, achieve high yields, and change the soil environment. The use of biofertilizer is needed to improve the quality and quantity of plants and reduce the chance of land degradation. The experimental design used was a randomized block design (RBD) with a single factor in fertilization. This RAK has nine treatment levels, namely: 1) control (without NPK and biofertilizer), 2) 100% NPK fertilizer, 3) 50% NPK fertilizer, 4) 100% NPK fertilizer + 100% biofertilizer, 5) NPK fertilizer 100% + 50% biofertilizer, 6) 50% NPK fertilizer + 100% biofertilizer, 7) 50% NPK fertilizer + 50% biofertilizer, 8) 100% biofertilizer, 9) 50% biofertilizer. This treatment was repeated five times. The use of NPK as a combination and substitution of biofertilizer. The basic fertilizer used, namely manure as much as 1.25 kg/tree. Overall, the best treatment was a combination of NPK fertilizer and biological fertilizer, especially in the P3 treatment, namely a combination of 100% NPK and 100% biological fertilizer. This can be seen in the vegetative growth of avocado plants and the soil's chemical and biological analysis, which have increased. Significant results occurred in plant height, the number of tertiary branches, total N, and soil invertase activity.